2019
DOI: 10.1111/conl.12631
|View full text |Cite
|
Sign up to set email alerts
|

The European trade ban on wild birds reduced invasion risks

Abstract: International wildlife trade is a major source of current biological invasions. However, the power of trade regulations to reduce invasion risks at large, continental scales has not been empirically assessed. The European wild bird trade ban was implemented in 2005 to counter the spread of the avian flu. We tested whether the ban reduced invasion risk in two European countries, where 398 nonnative bird species were introduced into the wild from 1912 to 2015. The number of newly introduced species per year incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 29 publications
0
40
0
Order By: Relevance
“…Such actions have already been used in the case of other taxa; for example, ‘The Wild Bird Act’ and ‘EU Wild bird ban’ have prevented the importation of exotic birds into the US since 1992, and Europe since 2005 ( https://www.fws.gov/le/USStatutes/WBCA.pdf ). In both cases, disease risk and impact on native birds was the stated case for regional bans 36 , and these same justifications exist in the case of reptiles 37 , 38 . Yet though undoubtedly effective in reducing global trade, unintended consequences such as shifting routes and markets 35 also demonstrate a more holistic approach is needed.…”
Section: Discussionmentioning
confidence: 82%
“…Such actions have already been used in the case of other taxa; for example, ‘The Wild Bird Act’ and ‘EU Wild bird ban’ have prevented the importation of exotic birds into the US since 1992, and Europe since 2005 ( https://www.fws.gov/le/USStatutes/WBCA.pdf ). In both cases, disease risk and impact on native birds was the stated case for regional bans 36 , and these same justifications exist in the case of reptiles 37 , 38 . Yet though undoubtedly effective in reducing global trade, unintended consequences such as shifting routes and markets 35 also demonstrate a more holistic approach is needed.…”
Section: Discussionmentioning
confidence: 82%
“…Overharvesting due to trapping for the international trade has caused large range contractions and decimated the populations, to the point that the species was included in Appendix 1 of CITES in 2017, prohibiting international trade on wild specimens for commercial purposes, and was listed as globally Endangered by IUCN in 2018 [48]. Although international bans have largely reduced the legal trade on parrots [42,49] and the upsurge of captive-breeding [6,49] has reduced the demand of wild-caught traded birds, illegal trade is still active [50], although at much lower volumes, including illegal trade on African grey parrots [51]. Nonetheless, while international trade is a matter of concern, less attention has been paid to the conservation impact of domestic trade on parrots, even though it is known to occur in different regions of the world, such as Madagascar [52], Asia [34], and all across the Neotropical region [9,23,35,38,39,[53][54][55][56][57].…”
Section: Conservation Implications Of Selective Parrot Poachingmentioning
confidence: 99%
“…Alternative sources can also be offered to satisfy the cultural tradition of owning pet parrots. Breeding parrots in captivity is well established [6], and can successfully supply the previous demand for internationally traded wild parrots [49]. Thus, breeding native parrots for local sale [9] could reduce the pressure on wild populations.…”
Section: Suggested Conservation Actionsmentioning
confidence: 99%
“…Although the effectiveness of wildlife trade bans has been contested (e.g., [ 10 , 11 , 82 ]), there are numerous examples of bans in current operation that demonstrate their practical value. For instance, in terms of conservation benefits, overall the EU ban on imports of wild-caught birds in 2005 is thought to have effectively reduced trade and biological invasion risk globally [ 79 , 83 ]. Similarly, Pain et al [ 84 ] reported that the US ban on imports of birds (on the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES) Appendices I and II) has had a positive impact on parrot conservation in the Neotropics.…”
Section: Moving Towards An End To the Wildlife Trade The Case Formentioning
confidence: 99%